Need, equity, and accountability - Alexander Max Bauer; Frauke Meyer; Jan Romann; Mark Siebel; Stefan Traub (Social Choice and Welfare, 2022)
We report the results of a vignette study with an online sample of the German adult population in which we analyze the interplay between need, equity, and accountability in third-party distribution decisions. We asked participants to divide firewood between two hypothetical persons who either differ in their need for heat or in their productivity in terms of their ability to chop wood. The study systematically varies the persons' accountability for their neediness as well as for their productivity. We find that participants distribute significantly fewer logs of wood to persons who are held accountable for their disadvantage. Independently of being held accountable or not, the needier person is partially compensated with a share of logs that exceeds her contribution, while the person who contributes less is given a share of logs smaller than her need share. Moreover, there is a domain effect in terms of participants being more sensitive to lower contributions than to greater need.
Keywords: 330; Economic Theory/Quantitative Economics/Mathematical Methods; Public Economics; International Political Economy; Game Theory; Economics; Social and Behav. Sciences; Social Policy